2013
DOI: 10.2306/scienceasia1513-1874.2013.39.472
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of essential oils and their active components from Thai spices against foodborne pathogens

Abstract: As the popularity of organic food especially fresh vegetables is increasing, it is a common practice to replace chemical fertilizers by manure which leads to high bacterial contamination. Some essential oils such as Thymus vulgaris (thyme) and Ocimum basilicum (basil) oils reduce spoilage flora and foodborne pathogens when used in washing water. This information prompted us to search for effective essential oils from Thai spices for vegetable washing products. Seven out of nine essential oils; fingerroot (Boes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
(29 reference statements)
0
18
0
2
Order By: Relevance
“…Natural antimicrobials have started slowly replacing addition of traditional antimicrobials such as different antibiotics to food and food products, due to increasing consumer awareness (Cetin‐Karaca and Newman ). So, there is an increasing demand to investigate the inhibitory effects of plant‐derived phenolics on different foodborne pathogens (Phanthong and others ). The objective of the present study was to determine the effect of the phenolic extracts from the seed coats of selected colored soybean cultivars on the growth of foodborne pathogens, Salmonella Typhimurium, E. coli O157:H7, and Campylobacter jejuni , in broth‐cultures as well as on chicken skin.…”
Section: Introductionmentioning
confidence: 99%
“…Natural antimicrobials have started slowly replacing addition of traditional antimicrobials such as different antibiotics to food and food products, due to increasing consumer awareness (Cetin‐Karaca and Newman ). So, there is an increasing demand to investigate the inhibitory effects of plant‐derived phenolics on different foodborne pathogens (Phanthong and others ). The objective of the present study was to determine the effect of the phenolic extracts from the seed coats of selected colored soybean cultivars on the growth of foodborne pathogens, Salmonella Typhimurium, E. coli O157:H7, and Campylobacter jejuni , in broth‐cultures as well as on chicken skin.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antimicrobial activity of some PCs including: thymol (Lambert et al, 2001;Santas et al, 2010), eugenol (Phanthong, Lomarat, Chomnawangb, & Bunyapraphatsaraa, 2013), carvacrol (Lambert et al, 2001;Santas et al, 2010), quercetin (Yao et al, 2011) and myricetin (Puupponen-Pimia et al, 2001) has been previously reported, the response after the long term exposure was not reported and there are still many unexplored sources. Moreover, thymoquinone and xanthohumol have not been included in antimicrobial studies and antimicrobial activity of chlorogenic acid, curcumin, (À ) epicatechin, eugenol, myricetin and rutin have not been reported broadly on pathogenic Salmonella and E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…cereus , E . coli , S. aureus and S. typhimurium (Phanthong et al ., ). Other than inhibiting bacteria, Kumar et al .…”
Section: Resultsmentioning
confidence: 99%